Mulberry Extract Inhibits Ferroptosis Through Antioxidant Activity, Iron Chelation, and Multi-Target Regulation: Insights from in Vitro and in Silico Study - Song, Kaidi; Li, Meng; Wei, Zhenlin (Scientific Journal of Technology, 2026)
Ferroptosis is a novel modifiable mode of cell death. Mulberry extract has antioxidant capacity, a hepatoprotective effect, and the ability to alleviate carbon tetrachloride-induced liver injury. However, whether it can complex iron ions and inhibit the activity of the key enzyme of Ferroptosis has not yet been reported. In this study, we used virtual screening, molecular docking, and molecular dynamics analysis to elucidate the anti-Ferroptosis components and mechanism of action in mulberry.